A case of agnogenic intrahepatic arterioportal fistula complicated by gastric ulcer bleeding and progressive portal thrombosis. Issue 1 (30th June 2022) - Yang, Siwei; Su, Tianhao; Zhang, Zhiyuan; Yu, Jianan; Jin, Long
Abstract: Arterioportal fistulas (APFs) are defined as vascular communications between the systemic arteries and portal circulation. APFs are classified as congenital or acquired, large or small, intrahepatic or extrahepatic, and traumatic or spontaneous. The consistent abnormal connection may result in severe presinusoidal portal hypertension, leading to gastrointestinal bleeding (GIB), ascites, elevated liver function enzymes, heart failure, diarrhea, and even pancreatitis or hematobilia in some unusual cases. Indeed, less than half reported cases have GIB, predominately caused by variceal rupture. Peptic ulcer bleeding has rarely been reported in the setting of APFs. Herein, we describe a case in which intrahepatic APF manifested as gastric ulcer bleeding, progressive portal thrombosis, and massive ascites, with these symptoms successfully relieved by endovascular treatment. Highlights: Arterioportal fistula (APF) leads to portal hypertension. The developmental intrahepatic AFP was reviewed by computed tomography (CT) images in this case. Peptic ulcer bleeding instead of variceal bleeding secondary to APF is rare. Endovascular treatment is a preferred treatment option for major APF types. Enhanced CT, endoscopy, and digital subtraction angiography are essential for differentiating the causes and managing APF‐related events. Abstract : Preoperative images showing (A) multiple gastric ulcers in the context of at gastric antrum, and (B) multiple esophageal varices. (C) Follow‐up endoscopic images of the gastric antrum after endovascular treatment. (D) Coronal CT image demonstrating the APF and enhancement of the main portal vein in the arterial phase. (E and F) Axial CT images showing newly developed thrombi in the main trunk (white arrow) and the left branch of the portal vein at 4 days after admission. (G) At 2 months after discharge, a cross‐sectional CT image in the portal vein phase shows a few residual thrombi in the main portal vein (white arrow), no thrombus in the left portal vein (not shown), and disappearance of the ascites. (H) Pre‐embolization digital subtraction angiography (DSA) demonstrating a fistula and reflux flow in the right portal vein branch in the arterial phase. (I) Post‐embolization DSA showing absence of fistula and reversal flow after embolization with steel coils and gelatin sponge particles (1000‐1400 um). APF, arterioportal fistula; CT, computed tomography; DSA, digital subtraction angiography; PHG, portal hypertensive gastropathy.